The cidade canção and João Pereira: Steps of the poet grain of sand at Teatro Caipira in northern Paraná (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The Teatro Caipira occurred during the 1960s and 1970s in the states of Paraná and São Paulo, and is far from being contemplated, with due importance, in the history of Brazilian theatre. The present article strives to fill the gap of a historiography of the Teatro Caipira and to understand its trajectory. For this, the life and career of the actor, poet and composer João Pereira, self-denominated poet grain of sand, is analyzed, as well as the piece Corisco antes de ser cangaceiro (1968), by the same artist, with the objective of apprehending the means of scenic production, dramaturgy and themes present in the Teatro Caipira. Finally, and beyond all, to keep alive the memory of João Pereira.
Keywords: Teatro Caipira; Popular theatre; History of actors; Maringá; Paraná theatre